2014
DOI: 10.4314/jab.v80i1.7
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric variation in the forest rodent <i>Malacomys edwardsi</i> (Rodentia: Muridae) in Côte d’Ivoire

Abstract: Objective: This study examined the intra-specific cranial morphometric variability between populations of Malacomys edwardsi from three distinct localities in Côte d'Ivoire. Methodology and results: The data set focused on 23 cranial measurements recorded on 158 skulls of M. edwardsi from Adiopodoumé (n = 43), Bolo (n = 34) and Taï (n = 81). Sexual and geographical variations were investigated using univariate and multivariate statistics. No sexual dimorphism was recorded. However highly significant morphometr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 11 publications
0
3
0
1
Order By: Relevance
“…This variability was also not dependent upon sex where the sex ratio was quite equilibrated (86 males versus 76 females). The absence of significant variability between populations based upon age and sexual dimorphism was also reported in numerous rodents such as Jaculus jaculus (Ben Faleh et al, 2010b, 2010c, Mastomys natalensis (Lalis et al, 2009), Rattus rattus (Ben Faleh et al, 2012a) and Malacomys edwardsi (Bohoussou et al, 2014). The 12 J. orientalis specimens that were previously karyotyped by Faleh et al (2010a; 2n = 48 and NFa varies from 84 to 88) have different skull morphometrics in the three climatic regions (or morphotypes).…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…This variability was also not dependent upon sex where the sex ratio was quite equilibrated (86 males versus 76 females). The absence of significant variability between populations based upon age and sexual dimorphism was also reported in numerous rodents such as Jaculus jaculus (Ben Faleh et al, 2010b, 2010c, Mastomys natalensis (Lalis et al, 2009), Rattus rattus (Ben Faleh et al, 2012a) and Malacomys edwardsi (Bohoussou et al, 2014). The 12 J. orientalis specimens that were previously karyotyped by Faleh et al (2010a; 2n = 48 and NFa varies from 84 to 88) have different skull morphometrics in the three climatic regions (or morphotypes).…”
Section: Discussionmentioning
confidence: 77%
“…Morphometric approaches have been shown to be powerful to analyze skull variability among rodents species (Chimimba, 2001;Nicolas et al, 2008;Lalis et al, 2009;Bezerra and De Oliveira, 2010;Ben Faleh et al, 2012a;Bohoussou et al, 2014). To date, no morphometric studies have reported on the skull variability of J. orientalis in Tunisia.…”
Section: Introductionmentioning
confidence: 99%
“…(2014) [35]. This suggests that males and females followed the same growth pattern, at least during one period of their development.…”
Section: Discussionmentioning
confidence: 92%
“…Conventional morphometrics which is based on analysis of distances (lengths and widths) has provided the methodological basis for non-geographic and geographic variation study in phenotypic morphological traits. Morphometric methods have been widely applied to investigate skull variation among rodent species (Ben Faleh et al 2012;Bezerra & De Oliveira 2010;Bohoussou et al 2014;Lalis et al 2009;Nicolas et al 2008), but no studies on craniodental measurements of R. rattus have been reported in Peninsular Malaysia.…”
Section: Introductionmentioning
confidence: 99%